Effects of dietary L-glutamine and glutamic acid combination, and whey powder on the performance and nutrient digestion in weaned piglets fed grain-based diets - dos Santos Almeida, Jonathan Mádson (2021)
Objective: The present study aimed to evaluate the influence of including L-glutamine along with glutamic acid as a supplement in weaned piglets' diets with and without whey powder. Methods: Two assays were carried out. A total of 40 piglets ([Landrace×Large White]× Pietrain) weaned at 24 days of age with an initial body weight of 6.6±0.6 kg were used in the first assay, and the following parameters were evaluated: Growth performance, the incidence of diarrhea, morphometry, intestinal integrity, and hepatic glycogen index. The animals were then blocked into four groups according to different diets: Diet all-grain feeding (G); diet all-grain feeding with whey powder (GW); and with vs without 1% supplementation of the commercial product containing L-glutamine and glutamic acid (A or NA). Whey powder was added according to the stage of life, corresponding to 17%, 10%, and 5%, respectively, in order to meet the need for lactose. The animals were evaluated at 24 to 42 days and at 24 to 55 days of age. The nutrient digestibility for the second assay was carried out by using 24 animals with an average weight of 11.49±1.6 kg, and the same diets were tested. Results: The supplementation of L-glutamine + glutamic acid or the addition of whey powder in diets for weaned piglets provided (p<0.05) greater feed intake, greater weight gain and improved feed conversion in the initial period (24 to 42 days age). However, in the whole period (24 to 55 days age) only amino acid supplementation affected (p<0.05) growth performance. There was a positive interaction (p<0.05) between the type of diet and L-glutamine + glutamic acid supplementation on villus height, crypt depth and the villus:crypt ratio in the duodenum. In addition, L-glutamine + glutamic acid supplementation reduced (p<0.05) the crypt depth and improved the villus:crypt ratio in the jejunum. The inclusion of whey powder affected (p<0.05) positively the digestibility coefficients analyzed except mineral matter digestibility coeficients. The supplementation of 1% the commercial product composed of L-glutamine and glutamic acid improved (p<0.05) only the digestibility coefficient of crude protein. Conclusion: These results indicate that supplementation of 1% commercial product containing L-glutamine + glutamic acid in diets for piglets from 24 to 55 days of age, dispenses with the use of whey powder when evaluating growth performance. Amino acid supplementation alone or associated with whey powder affects (p<0.05) positively the indicators of the intestinal integrity.